Innovation green business models in startups: Case study of the Algerian Startup Ecotashira - Mouna, Araar; Youcef, Abaidia; Mahyiddine, Mekahlia (International journal of economic perspectives, 2024)
This article explores the crucial role that startups play in fostering green business model innovation by identifying several key concepts and their interrelationships. Through a case study of the startup Ecotashira, which aims to provide innovative solutions in the field of sustainable vertical farming through its innovative product eco dalle tile, by analyzing their current business model, identifying strengths and weaknesses along with potential opportunities and threats and this enhancing the understanding of how these enterprises can contribute to driving sustainable development and the many challenges they face in the field of green innovation in Algeria, The findings of the study indicate that startups occupy a central role in providing innovative solutions that facilitate environmental conservation while enhancing economic productivity, helping existing organizations to change their traditional business models in strategic partnerships, and this helping to create a more sustainable future for future generations. The study concludes with key recommendations